2016
DOI: 10.3109/00498254.2016.1144896
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective hydroxylation by CYP2C19 and oxidation by ADH4 in thein vitrometabolism of tivantinib

Abstract: 1. In prior studies, it has been shown that tivantinib is extensively metabolized in humans to many oxidative metabolites and glucuronides. In order to identify the responsible enzymes, we investigated the in vitro metabolism of tivantinib and its four major circulating metabolites. 2. The primary isoforms involved in the elimination of tivantinib were CYP2C19 and CYP3A4/5. CYP2C19 showed catalytic activity for the formation of M5 (hydroxylated metabolite), but not for M4 (a stereoisomer of M5), whereas CYP3A4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Of note, ADH4 protein was also detected by Western blotting not only in cytosolic fractions but also in the microsomal fractions, although the latter band was faint. Nishiya et al (22) also reported that the ADH-catalyzing oxidation of hydroxyltivantinib was detected in human liver microsomes, as well as in the cytosol. Further analyses of the subcellular localization of ADH enzymes are therefore necessary.…”
Section: Alcohol Dehydrogenasementioning
confidence: 95%
See 1 more Smart Citation
“…Of note, ADH4 protein was also detected by Western blotting not only in cytosolic fractions but also in the microsomal fractions, although the latter band was faint. Nishiya et al (22) also reported that the ADH-catalyzing oxidation of hydroxyltivantinib was detected in human liver microsomes, as well as in the cytosol. Further analyses of the subcellular localization of ADH enzymes are therefore necessary.…”
Section: Alcohol Dehydrogenasementioning
confidence: 95%
“…A metabolite of celecoxib hydroxylated at the methyl group on the benzene ring by CYP2C9 is further oxidized by ADH1C and ADH4 (21). A metabolite of tivantinib hydroxylated at carbon atoms adjacent to benzene or the pyrrole ring by CYP3A is also oxidized by ADH1A and ADH4 (22). A hydroxylated metabolite of vortioxetine at the methyl group on the benzene ring by CYP2D6 is oxidized by ADH, although the isoform has not been identified (23).…”
Section: Alcohol Dehydrogenasementioning
confidence: 99%
“…Indeed, despite controversies regarding its mechanism of action, two phase II clinical trials (NCT01575522, NCT00988741) have demonstrated that tumors with high levels of MET present a high degree of response to tivantinib treatment[145,146]. In term of pharmacokinetics, tivantinib is metabolized by CYP2C19, CYP3A4/5, UGT1A9, and alcohol dehydrogenase isoform 4[147]. CYP2C19 shows catalytic activity for the formation of the hydroxylated metabolite (M5), whereas CYP3A4/5 catalyzes formation of M5 and its stereoisomer (M4).…”
Section: Pharmacogenetics Of Drugs Under Investigationmentioning
confidence: 99%
“…CYP2C19 shows catalytic activity for the formation of the hydroxylated metabolite (M5), whereas CYP3A4/5 catalyzes formation of M5 and its stereoisomer (M4). Moreover, CYP3A4/5 represents the major cytochrome isoform involved in the elimination of M4, M5, and the keto-metabolite (M8), and together with UGT1A9, involved in the glucuronidation of M4 and M5[147]. Finally, the alcohol dehydrogenase isoform 4, through a sequential keto-metabolite of M4 and M5 and through M8, leads to the formation of M6[147].…”
Section: Pharmacogenetics Of Drugs Under Investigationmentioning
confidence: 99%
See 1 more Smart Citation